Civil resistance campaign for the Free Papua Movement and student protests in 2019 in Surabaya, Indonesia. Issue 1 (2nd January 2023) - Saud, Muhammad; Ashfaq, Asia
ABSTRACT: The Papuan Freedom Movement is well known for its ethnic and regional conflicts in Indonesia. This article aims to narrate youth participation in civil resistance protests in Surabaya, Indonesia. These protests grabbed the attention of the media and other international partners discussing the issue of Papuans' freedom. Many protests were organised around the world to sensitise government, media and human rights activists to revisit the decision made regarding Papuans which was documented in 1964. The conceptual method was deployed and material was gathered from previous studies, such as newspapers, video clips, articles, and books on civil resistance and Papuan conflicts. The results show that, due to a lack of coordination between the government and protesters, Papuan youth was aggressive during the civil resistance in the August 2019 events. There should be a new kind of platform that can specifically invite youth and educated scholars to build and develop strong coordination between Indonesian politicians and the leaders of the Free Papuan Movement. The findings suggest that the government of Indonesia and conflicting parties need to engage in peaceful dialogue to create a roadmap towards prosperity, development and harmony.